2018
DOI: 10.1177/2050640617752207
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of histological activity in patients with ulcerative colitis in deep remission: A prospective multicenter study

Abstract: In patients with UC in clinical and endoscopic remission, histological activity is an independent risk factor for clinical relapse. Further prospective studies need to clarify whether treatment optimization is justified in this context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 30 publications
1
49
0
Order By: Relevance
“…These differences between studies may reflect the influence of the microbiome and/or the animals’ age, as previously reported in experimental DSS colitis[ 27 , 28 ]. In addition, it has been reported that UC patients in clinical and endoscopic based remission presenting with active histological inflammation possess a higher risk for clinical relapse[ 29 , 30 ]. In this way, our study may provide an understanding of the pathological and clinical response of severe human UC, with higher chances of relapsing and chronic disease.…”
Section: Discussionmentioning
confidence: 99%
“…These differences between studies may reflect the influence of the microbiome and/or the animals’ age, as previously reported in experimental DSS colitis[ 27 , 28 ]. In addition, it has been reported that UC patients in clinical and endoscopic based remission presenting with active histological inflammation possess a higher risk for clinical relapse[ 29 , 30 ]. In this way, our study may provide an understanding of the pathological and clinical response of severe human UC, with higher chances of relapsing and chronic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data, however, indicates that MES 1 is not completely normal with regards to inflammatory histological state [6]. This increases the risk of relapse [7] and later complications. To achieve complete inflammatory remission, the aim should be MES 0.…”
Section: Introductionmentioning
confidence: 99%
“…Data from rigorously designed, adequately powered studies are required to definitively address the role of colonic location with respect to biopsy procurement strategies in ulcerative colitis. Furthermore, while previous studies 4,11,12,20,21 have demonstrated that histological remission is a predictor of reduced risk of relapse in ulcerative colitis, longitudinal studies are needed to determine whether proximal, compared to distal, biopsies are relatively more predictive of outcome.…”
Section: Discussionmentioning
confidence: 99%